Medical Treatment of Cushing's Disease: An Overview of the Current and Recent Clinical Trials - Pivonello, Rosario; Ferrigno, Rosario; De Martino, Maria Cristina; Simeoli, Chiara; Di Paola, Nicola; Pivonello, Claudia; Barba, Livia; Negri, Mariarosaria; De Angelis, Cristina; Colao, Annamaria (Frontiers in Endocrinology, 2020)
Cushing’s Disease (CD) is an endocrine disorder caused by an ACTH-secreting pituitary adenoma, with consequent chronic hypertcortisolemia due to excessive adrenal gland stimulation. CD presents a severe clinical burden, with an higher mortality rate compared to healthy population and a reduced quality of life. Neurosurgery represent the first-line therapy, but unfortunately disease persistence or recurrence may occur in up to 30% of patients. Among second line treatments, medical therapy is gradually gaining importance as a therapeutic option, although the current medical treatment are unable to reach optimal efficacy and safety profile. Therefore, new drugs and new formulation of already available drugs are currently under clinical investigation in worldwide clinical trials, in order to assess their effects in CD treatment. In the current review, we will provide a summary the currently available evidences from on-going and recently finished clinical trials on CD all over the world, with a specific focus on preliminary data.